(3GdKQhI GdWHjYjI ddCee (B:s (3JWhjY GdShb dGMJjGLGJ GdHjFI (B/s - (3QhOeGf, OGajO eGdjfs; (3MSfj(B;Roodman.David Mlins ((3GdbGgQI (B:s (3GdLeYjI GdeUQjI dfTQ GdeYQaI h GdKbGaI GdYGdejI ,s, 1999)
(3jcTa cJGH GdKQhI GdWHjYjI ddCee GdfbGH Yf gPg GdfXe h jdbi GdVhA Ydi eG jdMb efgG GcHQ GdVQQ HGdHjFI h HGdEbJUGO h jbJQM GdMdhd h ef Hjf gPg GdMdhd aQV Kef efGSH deG JbOeg GdWHjYI ef NOeGJ h Med GdedhKjf ddHjFI Ydi OaY ebGHd GdOeGQ GdPj jSHHhfg h aj HYV GdGMjGf OaY eHGdZ ddfGS h ddCYeGd MJi dG jdhKhf hjMOhfG cHjQ GdCed aj Gf JSGYO gPg GdcJH GdfGS Ydi WQjbJge GdNGU fMh YGde GcKQ GSJbQGQG h GSJOGeIs
Keywords: (3GdKhQI GdWHjYjIs; (3GdJdhKs